The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1128/aac.45.11.3109-3112.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activities of New Macrolides and Fluoroquinolones against Mycobacterium ulcerans Infection in Mice

Abstract: Mice infected in the left hind footpad with 5 log 10 acid-fast bacilli of Mycobacterium ulcerans were divided into an untreated control group and 17 treatment groups that received one of the following regimens for 4 weeks (all doses in milligrams per kilogram): 100 mg of azithromycin (AZM), 100 mg of clarithromycin (CLR), or 50 mg of AZM for a duration of 5 days a week (daily), three times a week, or once weekly. In addition, the following regimens were administered daily: 100 mg of telithromycin (TLM), sparfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 16 publications
2
64
0
Order By: Relevance
“…ulcerans has been shown in vitro to be susceptible to rifampin (17), aminoglycosides, macrolides (25), and quinolones (30). It was susceptible to the same drugs in the mouse footpad model (7,11,29), but clarithromycin and quinolones were bacteriostatic whereas rifampin, amikacin, and streptomycin appeared to be bactericidal (10); the size of mouse footpad lesions treated with rifampin and amikacin together for 12 weeks decreased progressively, the mean CFU counts of M. ulcerans were reduced, and there were no relapses (10,21).…”
mentioning
confidence: 96%
“…ulcerans has been shown in vitro to be susceptible to rifampin (17), aminoglycosides, macrolides (25), and quinolones (30). It was susceptible to the same drugs in the mouse footpad model (7,11,29), but clarithromycin and quinolones were bacteriostatic whereas rifampin, amikacin, and streptomycin appeared to be bactericidal (10); the size of mouse footpad lesions treated with rifampin and amikacin together for 12 weeks decreased progressively, the mean CFU counts of M. ulcerans were reduced, and there were no relapses (10,21).…”
mentioning
confidence: 96%
“…Traditionally, BU was managed by surgical excision with or without skin grafting. Antimicrobial therapy was thought to be ineffective until experiments in the mouse footpad model demonstrated the efficacy of combinations composed of an aminoglycoside and rifampin (RIF) (2,6,13). Subsequent clinical experience has confirmed that 2 months of streptomycin (STR) and RIF is the treatment of choice for all forms of BU, although adjunctive surgery may be necessary to heal large ulcers (4,7,12,14).…”
mentioning
confidence: 99%
“…In vitro, M. ulcerans has been shown to be susceptible to rifampin (13), aminoglycosides (7), macrolides (21), and quinolones (26). Infection of mouse footpads has been used as a model for susceptibility testing, and after treatment with the same antibiotics, the lesions became smaller and the total number of M. ulcerans organisms in tissue was reduced (2,8,25). The combination of rifampin with amikacin or streptomycin for 8 weeks has been the most effective in reducing the bacterial load in a number of studies, and the low relapse rate after treatment suggested that this combination was bactericidal (2,15).…”
mentioning
confidence: 99%